2016
DOI: 10.1111/dme.13063
|View full text |Cite
|
Sign up to set email alerts
|

First report on the nationwide incidence and prevalence of Type 1 diabetes among children in Turkey

Abstract: This is the first study to report the incidence and prevalence of Type 1 diabetes in children in Turkey. The incidence of Type 1 diabetes reflects the geographical location of Turkey, bridging Asia and Europe, with the incidence being higher than in Asia but lower than in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 19 publications
5
38
0
7
Order By: Relevance
“…No seasonal pattern was identified in this study, unlike a previous report from Turkey where onset was more common in winter and autumn [22]. A small female preponderance has been found in Turkey [19] and particularly in Uzbekistan [20]. However, this Azerbaijan data showed a slight male excess, in agreement with the prior published series from Azerbaijan [3].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…No seasonal pattern was identified in this study, unlike a previous report from Turkey where onset was more common in winter and autumn [22]. A small female preponderance has been found in Turkey [19] and particularly in Uzbekistan [20]. However, this Azerbaijan data showed a slight male excess, in agreement with the prior published series from Azerbaijan [3].…”
Section: Discussionsupporting
confidence: 84%
“…Almost all (98%) subjects in this study were diagnosed with type 1 diabetes. The pattern of type 1 diabetes of Azerbaijan is similar to that of European [1] and Turkic [19 20] populations in terms of the peak age of onset and corresponds with an almost uniform presence of classic symptoms [1]. No seasonal pattern was identified in this study, unlike a previous report from Turkey where onset was more common in winter and autumn [22].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, type 1 DM prevalence was 0.75/1000, higher in girls than in boys. In Turkey, type 1 DM incidence is in accordance with the geographical location of this country, higher than in Asia, but lower than in Europe [21].…”
Section: Dm and Prediabetes Prevalence/ Incidence In Different Countrmentioning
confidence: 61%
“…Nevertheless, in a limited number of regions showing significant sex distinction, propensity exists that male preponderance is mainly present in populations with higher risk for T1D such as Caucasians while a female excess is commonly found in lower risk groups like Africans and Asians . With respect to studies extending such epidemiological research into patients diagnosed over 15 years of age, a consistent male predominance has been identified in the United Kingdom, Republic of Srpska, Slovenia, Israel, and China with the only exception of a Turkish study reporting a constant female dominance throughout 0 to 18 years . In a systematic review on a collection of 54 studies reporting T1D incidences in individuals diagnosed over the age of 15 throughout the world, 44 (81%) studies showed larger incidences in males, and the overall male‐female ratio was calculated to be 1.47 .…”
Section: Epidemiologymentioning
confidence: 99%